E-Jobsheet Based on Mobile Pocket Book as Digital Learning Resources (DLRs) - Agariadne Dwinggo Samala; Muhammad Giatman; Wakhinuddin Simatupang; Fadhli Ranuharja (Jurnal Teknologi Informasi dan Pendidikan, 2021)
This study aims to develop an E-jobsheet based on a mobile pocket book in the form of a digital pocket book on algorithms and basic programming courses. This research is a Research & Development (R&D) research with the Borg & Gall development model which consists of 10 stages, but in this research, the researcher limits it to producing an initial product in the form of an initial product or to the 5th stage, namely main product revision. The research instrument in collecting data used validation questionnaires, response questionnaires, and unstructured interviews to users during small-scale trials. The data analysis used in this research is descriptive data analysis with a quantitative approach. Based on the validation results from the media and material aspects, the overall product validity level is 85.46% with a valid category, the student response rate in a small-scale trial of the E-jobsheet is 86% with a very good category. So, it can be stated that the E-jobsheet based on the mobile pocket book that was developed is valid and suitable for further use on a wider scale.